Recollection and Rumination of Memories: A Study of Kazuo Ishiguro’s An Artist of the Floating World - Rana, Meenakshi (International Journal of Advanced Science and Technology, 2020)
The present paper explains the notion of recollections and rumination of memories in the novel An Artist of the Floating World that is connected to the past life of the characters. An Artist of the Floating World is the story that gives the details of time after World War Second by the narrator of the novel. Kazuo Ishiguro explores the opinion that how memories affect the life of human beings in the present time. The main protagonist of the novel is Masuji Ono who plays the role of father and grandfather. The novel elucidates the notion of Japanese culture, the conflict in generations, the loss and World War II with the help of reminiscence with the reflection of memories in his life. The character of Ono explains his sense of guilt and he worked in the nationalist government in the time period of war. The present study firstly explores that how the characters of the novel suffer or living a conflicted life because of memories and secondly how with the help of recollections of memories and rumination the narrator interprets the whole story to the readers.